Periodic time-domain analysis based on approximation by splines and harmonic balance - Bartkevicius, S. (Elektronika ir Elektrotechnika, 1999)
A periodic solution of non-linear system represented by cubic spline may be expressed by a finite harmonic row exactly representing nodes of the spline. The differentiation operation on this row is replaced by multiplication by special matrix. New representation of a periodic solution allowing direct differentiation is proposed.